You can too - Mary C Crowley (Flemming H. Revell Co, 1980)
The realization of this true helped a young orphan girl, Mary C. Crowley, lift herself out of poverty and despair. With the sheer determination that comes from an unflagging Christian faith, she became one of the country's most successful businesswomen - a radiantly fulfilled human being.